Cavum septum pellucidum and first-episode psychosis: A meta-analysis. - Hanwen Liu; Ling Li; Li Shen; Xianliang Wang; Yazhu Hou; Zhiqiang Zhao; Lili Gu; Jingyuan Mao (PLoS ONE, 2017)
To investigate the prevalence and changes of cavum septum pellucidum (CSP) in first-episode psychosis (FEP) patients.Medline, Embase, and the Cochrane Central Register of Controlled Trials (CENTRAL) were searched to identify eligible studies comparing FEP patients and healthy controls from inception to Feb 29, 2016.Ten cross-sectional studies and three longitudinal studies reported in ten articles met our criteria. Our meta-analysis found no significant differences in the prevalence of either "any CSP" (OR = 1.41; 95% CI 0.90-2.20; p = 0.13; I2 = 52.7%) or "large CSP" (OR = 1.10; 95% CI 0.77-1.58; p = 0.59; I2 = 24.1%) between FEP patients and healthy controls. However, the heterogeneity analysis of the prevalence of "any CSP" suggested bias in outcome reporting.The results based on current evidence suggest it is unclear whether "any CSP" is a risk factor for FEP due to the heterogeneity of the studies. There is insufficient evidence to support that "large CSP" is a possible risk factor for FEP.